Implementasi Kebijakan Pengadaan Guru Pendidikan Agama pada Sekolah di Kota Samarinda Provinsi Kalimantan Timur - Mujizatullah Mujizatullah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This article explains the Implementation of the Policy on Procurement of Religious Education Teachers in Schools in Samarinda Municipality, the East Kalimantan Province. This is a descriptive-qualitative research. The research results showed that there was poor communication between the Department of Education and the Ministry of Religion in relation to the preparation and proposed formation and determination of civil servants in religious teachers procurement. There is a different understanding in each institution. It shows that there is sectorial egos arises between each ministry. The Ministry of Religion as a vertical institution the madrassas and the Education Office of schools should arrange synergizing in the procurement of religious teachers. Therefore, both institution require an MOU between the Regional Government and the Ministry of Religion regarding the formation of the appointment of religious teachers both CPNS and the appointment of religious teachers THL (Tenaga Harian Lepas - Freelance Daily Workers).